Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1186/1472-6963-11-305
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare costs in patients with metastatic lung cancer receiving chemotherapy

Abstract: BackgroundTo characterize healthcare resource utilization and costs in patients with metastatic lung cancer receiving chemotherapy in the US.MethodsUsing data from a large private multi-payer health insurance claims database (2000-2006), we identified all patients beginning chemotherapy for metastatic lung cancer. Healthcare resource use (inpatient, outpatient, medications) and costs were tallied over time from date of therapy initiation ("index date") to date of disenrollment from the health plan (in most ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 10 publications
2
24
1
3
Order By: Relevance
“…Hospitalization and outpatient chemotherapy were confirmed as the main cost drivers in lung cancer care (e.g., [6,18]). In our sample, spending on outpatient chemotherapy did not increase over time-contrary to a study in individuals all with metastatic lung cancer [19]. Thus, the application of cost-intense innovative targeted therapies as some kind of ultima ratio might only apply for some subpopulation of lung cancer patients.…”
Section: Discussioncontrasting
confidence: 90%
“…Hospitalization and outpatient chemotherapy were confirmed as the main cost drivers in lung cancer care (e.g., [6,18]). In our sample, spending on outpatient chemotherapy did not increase over time-contrary to a study in individuals all with metastatic lung cancer [19]. Thus, the application of cost-intense innovative targeted therapies as some kind of ultima ratio might only apply for some subpopulation of lung cancer patients.…”
Section: Discussioncontrasting
confidence: 90%
“…39 Another retrospective study of utilization and costs associated with adult patients with metastatic lung cancer (not specific to NSCLC) found that 72% of patients had a hospitalization after the initiation of chemotherapy. 15 Although the characteristics and inclusion/exclusion criteria used in our study are differ- ent from these studies, our findings do confirm that a large proportion of patients with advanced lung cancer are hospitalized after initiating a variety of chemotherapy regimens. Our study adds to the literature by providing the distribution of outcomes by chemotherapy regimen.…”
Section: Discussionsupporting
confidence: 43%
“…15 These studies did not assess hospitalization specifically after bevacizumab treatment. Describing the patterns of toxicity profiles and hospitalizations associated with bevacizumab use in a community setting is important because it directly addresses the need for more clinically relevant information regarding the potential balance of benefits and harms for an expensive drug that may confer only limited improvements in survival.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, provider payments under Medicare are significantly less than commercial insurance reimbursement rates [110]. In a study of metastatic lung cancer patients that did not distinguish costs between lines of therapy, the mean total healthcare costs averaged US$125,849 over 500 days in 2000-2006 [15]. The mean second-line therapy costs over 12 months were US$35,032-75,310 for lung cancer patients receiving treatment in 2002-2006 [3].…”
Section: Research Article Henk and Raymentioning
confidence: 99%